Synthesis of indolizidine, pyrrolizidine and quinolizidine ring systems by proline-catalyzed sequential alpha-amination and HWE olefination of an aldehyde - Kauloorkar, Shruti Vandana; Jha, Vishwajeet; Kumar, Pradeep (RSC Advances, 2013)
A general procedure for the synthesis of azabicyclic ring systems viz. indolizidine, pyrrolizidine and quinolizidine has been developed utilizing proline-catalyzed sequential alpha-amination and Horner-Wadsworth-Emmons (HWE) olefination of an aldehyde as the key step. This method can be further extended to the synthesis of various biologically active natural products containing azabicyclic ring systems.